Analiz rezul'tatov pobeditelej meždunarodnych sorevnovanij na distancii 400 metrov kompleksnym plavaniem 2008-2019 godov - Galyautdinova, L. R.; Galyautdinov, M. I.; Lobanov, A. S.; Sitdikov, A. M.; Safina, R. M. (Uchenye zapiski universiteta imeni P.F. Lesgafta, 2019)
The analysis of the 50-meters line segments, average and standard deviation of cycle time of the winners in the 400 m individual medley distance at the period of 2008 - 2019 years Olympic Games, and the World Championships in Water Sports. The best time line-segments T, the largest and the smallest average time of cycles, the largest and the smallest standard deviation of cycles was defined for those researched competitions. Based on that analysis the result of 2017 world championship winner Kalisz Chase was noted on the 5th and 6th line-segments, because results are better in comparison with the studied. The analysis of variance method with StatPlus6 program investigated the significance of differences indicators and their posterior comparisons are made. For the same indicators, Pearson correlation coefficients were calculated. Their strong correlation was noted among the winners of the World Championships 2015 and 2017 Seto Daiya and Kalisz Chase, respectively.